Exploring environmental issues : an integrated approach - Kemp, David D., 1943- (Routledge, 2004)
This book provides a key to understanding our potential environmental crisis : the concise, introductory text presents a review of current issues using a geographical approach that stresses the interrelationships between environment and societies.